2020
DOI: 10.1155/2020/8392832
|View full text |Cite
|
Sign up to set email alerts
|

Admission Decisions Made by Emergency Physicians Can Reduce the Emergency Department Length of Stay for Medical Patients

Abstract: Background. Emergency department (ED) overcrowding is a worldwide problem that poses a threat to patient safety by causing treatment delays and increasing mortality. Consultations are common and important in the emergency medicine profession and are associated with longer ED length of stay (LOS). The purpose of this study was to evaluate the impact of admission decisions by emergency physicians without consultations on the ED LOS and other quality indicators. Methods. The study was a retrospective observationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Among the six before–after studies, despite high heterogeneity (I 2 = 99%) in the pooled analysis (MD −0.99, 95% CI −1.43 to –0.56), five of the studies reported a significant decrease in ED LOS among patients in the groups where consultations were bypassed compared to control patients (see Figure 5). 24,25,27,37,38,41 Finally, one cohort study also reported a significant decrease in ED LOS among intervention patients (MD −4.34, 95% CI −4.61 to –4.07; see Figure 5). 26 …”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Among the six before–after studies, despite high heterogeneity (I 2 = 99%) in the pooled analysis (MD −0.99, 95% CI −1.43 to –0.56), five of the studies reported a significant decrease in ED LOS among patients in the groups where consultations were bypassed compared to control patients (see Figure 5). 24,25,27,37,38,41 Finally, one cohort study also reported a significant decrease in ED LOS among intervention patients (MD −4.34, 95% CI −4.61 to –4.07; see Figure 5). 26 …”
Section: Resultsmentioning
confidence: 90%
“…The majority of the included studies were conducted in North America (United States n = 12, 16–28 Canada n = 6 29–34 ) with a smaller number of studies conducted in Asia (South Korea n = 5, 35–39 Singapore n = 2, 40,41 Thailand n = 1, 42 Taiwan n = 1, 43 India = 1 44 ) and Europe (Ireland n = 1, 45 Turkey n = 2, 46,47 ; see Table 1). The studies were mainly conducted in a single ED site 16–25,27,29–32,34–50 . The majority of studies utilized a before/after study design ( n = 25, 71%), of which one study used a controlled before/after design 39 .…”
Section: Resultsmentioning
confidence: 99%
“…The strike assessed in this study involved not only EM residents but also residents in all the other departments; therefore, specialist consultants participated in decision-making at an earlier stage than normal. We also found that the number of consultations per patient, which is considered to play a key role in delaying EDLOS [ 24 , 25 ], was substantially reduced. It can be assumed that decisions made by EM specialists and the earlier involvement of specialists from other departments contributed to decreased EDLOS.…”
Section: Discussionmentioning
confidence: 99%
“…Detsky et al suggested that the volume of tests performed in teaching hospitals is more likely related to the case mix and severity of illness of patients admitted to these institutions than to a pure "teaching effect" [13]. While a previous report by Choi et al reported admission rates among ED patients of 10.2-27.6% [25], the admission rate of the ED in this study was much higher: 46.2% in the control period and 47.8% in the strike period. Reflected by the Emergency Medicine International emergency admission rate, the severity of the study ED population was high; therefore, although the ED was operated by specialists without trainees, the necessity of diagnostic tests did not change and the frequency of tests was maintained.…”
Section: Management Processmentioning
confidence: 99%
“…A prolonged ED length of stay (LOS) contributes to overcrowding, and its consequences include decreased quality of treatment, misuse of medical resources in the ED, decreased patient satisfaction [12], and an increased risk of infection transmission. It has been studied once that admission decisions regarding medical patients made by emergency physicians without specialty consultations in the ED reduce the LOS without a significant negative effect on mortality or hospital LOS [13].…”
Section: Ed Consultation and Admissionmentioning
confidence: 99%